2011
DOI: 10.1108/17542411111130990
|View full text |Cite
|
Sign up to set email alerts
|

Career attitudes and subjective career success: tackling gender differences

Abstract: Purpose -The purpose of this paper is to analyze the effect of gender upon the relation between protean and boundaryless career attitudes and subjective career success, in today's dynamic and changing organizational context. Design/methodology/approach -Data were collected using a questionnaire conducted on 150 graduate and post-graduate distance learning students. The data were analyzed using structural equation modeling. Findings -The analysis indicates that women's career success is positively related with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 66 publications
1
43
0
Order By: Relevance
“…Previous empirical studies have explored the relationship between protean career and career related outcomes such as career decision, career satisfaction and career advancement. Mixed results were found as the studies were conducted in different environmental contexts and sample population (Sullivan & Arthur, 2006;Enache, Sallan, Simo, & Fernandez, 2011). Moreover, the previous literatures have mainly focused on protean career as a predictor of career-related outcomes, whereas, there is lack of protean career literature studies that examines theoretically based variables to predict the protean career (Gubler, Arnold, & Coombs, 2013).…”
Section: Introductionmentioning
confidence: 74%
“…Previous empirical studies have explored the relationship between protean career and career related outcomes such as career decision, career satisfaction and career advancement. Mixed results were found as the studies were conducted in different environmental contexts and sample population (Sullivan & Arthur, 2006;Enache, Sallan, Simo, & Fernandez, 2011). Moreover, the previous literatures have mainly focused on protean career as a predictor of career-related outcomes, whereas, there is lack of protean career literature studies that examines theoretically based variables to predict the protean career (Gubler, Arnold, & Coombs, 2013).…”
Section: Introductionmentioning
confidence: 74%
“…Ng et al's (2005) meta-analysis determined that four broad categories of antecedents (human capital investments, organizational sponsorship, stable individual differences, and demographic characteristics) are associated with objective and/or subjective career success. Subsequent research has generally confirmed the relevance of these antecedents while incorporating additional predictors beyond those examined in Ng et al's meta-analysis (Abele & Spurk 2009, De Vos et al 2011, Enache et al 2011. Moreover, observations that some antecedents more strongly predict objective success and others predict subjective success and that many relationships between antecedents and success are moderated by individual or contextual factors (Greenhaus & Callanan 2013, Ng et al 2005 highlight the complexity of the career success process.…”
Section: Career Successmentioning
confidence: 81%
“…Career satisfaction was assessed at Time 1 and Time 2 with the five-item Career Satisfaction Scale (Greenhaus, Parasuraman, & Wormley, 1990; Italian version: Sarchielli & Toderi, 2005; Spanish version: Enache, Sallan, Simo, & Fernandez, 2011). Each item was measured on a scale from 1 ( strongly disagree ) to 5 ( strongly agree ; e.g., “I am satisfied with the success I have achieved in my career”).…”
Section: Methodsmentioning
confidence: 99%